2013
DOI: 10.1080/00222933.2013.825021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal occurrence and adaptation of the exoticGlycaspis brimblecombeiMoore (Hemiptera: Aphalaridae) in Italy

Abstract: Alien insects usually adapt their phenology and their needs to the environment into which they are introduced. During 2010, the red gum lerp psyllid, Glycaspis brimblecombei, was accidentally introduced into Italy, becoming an invasive pest of Eucalyptus L'Hér. Eucalypts are very common in Italy as ornamental and forest species. The seasonal adaptation of the psyllid was studied at three field sites. G. brimblecombei showed a seasonal population dynamic, suggesting that many generations occur during the year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
1
14
0
3
Order By: Relevance
“…Similarly, Laudonia et al . (), when studying seasonal occurrence of G. brimblecombei in Italy, showed that rain during summer and after a dry period was favourable for psyllid population increase. The results of the present study do not support, nor do they reject the influence of rainfall in psyllid abundance, presumably because there are no distinct periods of rainfall and drought in the study area.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Laudonia et al . (), when studying seasonal occurrence of G. brimblecombei in Italy, showed that rain during summer and after a dry period was favourable for psyllid population increase. The results of the present study do not support, nor do they reject the influence of rainfall in psyllid abundance, presumably because there are no distinct periods of rainfall and drought in the study area.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies conducted with G. brimblecombei in other countries indicate that temperature is the main factor involved in population dynamics of this psyllid (Paine, Millar & Hoddle, 2000; Ramirez, Mancera & Guerra-Santos, 2003; Laudonia, Magiotta & Sasso, 2014). Under laboratory conditions in Brazil, Firmino found that 26 °C is the optimal temperature for the development and reproduction of G. brimblecombei .…”
Section: Discussionmentioning
confidence: 99%
“…Psyllid nymphs produce honeydew after initial feeding and use it with a wax secretion to build tapered protective white shelters (lerp) on the leaf surface (Sharma et al, 2013). G. brimblecombei has five nymph instars, with a complete lifecycle from 15 to 34 days, and several generations per year (Firmino-Winckler et al, 2009; Laudonia, Magiotta & Sasso, 2014). There are no records of diapause for this psyllid species, even during the winter in temperate countries (FAO, 2012; Laudonia, Magiotta & Sasso, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study aimed to characterize this new Cardiaspina and E. moluccana interaction, and to determine the main biotic and abiotic factors influencing the population dynamics during the peak of this outbreak and any subsequent decline. Temperature is known to have a strong influence on aphid populations (Dixon, ) and has been reported to influence population abundance in psyllids (Laudonia et al ., ). Outbreaks of Cardiaspina species are known to result in severe defoliation of their host plants (Clark, ) as a result of psyllid‐induced leaf senescence (Steinbauer et al ., ).…”
Section: Introductionmentioning
confidence: 97%